GSM based dual power enhanced LED display notice board with motion detector - Kasilingam, Gowrishankar; Nithiyananthan, K; Ramesh Mani, Priyanka; Thomas, Sunil (International Journal of Engineering and Technology, 2018)
In this paper, a new improved Light Emitting Diode (LED) Display notice board with GSM technology has been created to plugs in all the drawbacks in existing framework. The proposed model has an excellent display notice board to display notices or messages at places that require real-time visibility, thereby transferring messages by Short Message Service (SMS) through cellular device. The proposed work in this paper elaborately narrates the procedure to construct a display notice board that has the quality of displaying messages in continuously running mode, and enabling the user to alter the ongoing message using SMS instantaneously. This system also has the feasibility to bind with other devices such as PC or laptop. The best feature of proposed system is the dual system for changing messages. And also utilizes two way power supply such as Renewable energy (Solar Power) and AC power. This feature enables the proposed model to work under any situations which overcomes the drawback in the existing display notice boards. Additionally, a motion detector has been included which turn ON or OFF the system automatically if any motion is not sensed.